Global invasive alien plant management lists: Assessing current practices and adapting to new demands - Fei-Fei Li; Qiang Hao; Xia Cui; Ruo-Zhu Lin; Bin-Sheng Luo; Jin-Shuang Ma (Plant Diversity, 2025)
Invasive alien species (IAS) significantly threaten global biodiversity and ecosystem stability. Despite increasing management efforts, a critical knowledge gap existed in understanding commonalities and disparities among national strategies. We analyzed several IAS management lists from 23 countries and the European Union, focusing specifically on vascular plant species within these lists. List composition, characteristics, and associated management measures were analyzed. Key patterns in species prioritization across national lists and intercontinental exchange of invasive alien plants (IAPs) were identified. Pistia stratiotes, Pontederia crassipes, Salvinia molesta, Cabomba caroliniana, Ulex europaeus were identified as globally recognized threats, being listed by at least 33.3% of analyzed countries and invading five or more continents. Aquatic plants were found to be more frequently included in management lists. A significant directional invasion pattern between the Eastern and Western Hemispheres was identified. Species native to Asia were observed to dominate as significant donors of IAPs across continents. The analysis of list management strategies highlighted substantial gaps in achieving Target 6 of the Kunming-Montreal Global Biodiversity Framework, particularly in species prioritization and inclusion of potential IAPs. In response to these challenges, a tiered classification system for invasive alien species list was proposed, encompassing High-Priority, Watchlist, Potential, and Priority Site categories, which aimed at enhancing management effectiveness by tailoring strategies to different invasion stages and ecological contexts. This study could contribute to understanding global IAPs management strategies and serve as a reference for policymakers and conservation managers to identify priority IAPs and refine management approaches.